A strong visible line in the spectrum of W11+. (1st September 2016) - Li, M; Qiu, M; Xiao, J; Yao, K; Brage, T; Hutton, R; Zou, Y
Abstract: We have investigated the visible spectrum of W 11+ and found a very strong line at the wave length of 527.61 nm from the 4f 13 5s 2 5p 2 ( 2 F7/2 - 2 F5/2 ) transition. We show that this line is strong since the excitation energy of the upper level opens up the possibility to capture a large population. We discuss the possibility that this strong line could be the unknown line seen in charge exchange spectra recorded at the JET fusion facility.